Peranan Kepolisian dalam Penerapan Restorative Justice terhadap Pelaku Tindak Pidana Pengeroyokan yang Dilakukan oleh Anak dan Orang Dewasa - Haryanto Ginting; Muazzul Muazzul (Jurnal Ilmiah Penegakan Hukum, 2018)
The Role of the Police in the Application of Restorative Justice to Perpetrators of Criminal Offenses Conducted by Children and Adults The rise of cases of brawl between high school students and even not only between high school students, but also has hit up to campuses, this often happens in big cities such as Jakarta, Surabaya, and Medan. This study aims to determine the role of the Police in implementing Restorative Justice against perpetrators of criminal acts of beating carried out by children and adults that occurred in the District of Namo Rambe District of Deli Serdang. The research method is done by using descriptive qualitative method that is normative. Based on the data obtained in the results of this study, the authors draw conclusions as follows: The criminal justice system must always promote the importance of law and justice. But there is a false view that the measure of the success of law enforcement is only marked by the success of bringing a suspect to court and then being sentenced. The measure of success of law enforcement by law enforcement officers should be characterized by the achievement of values of justice in the community. The police as a state tool that plays a role in enforcing the law is expected to be able to respond to this by implementing a Restorative Justice mechanism.